2010
DOI: 10.1002/asia.201000496
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Aqueous Solution Synthesis of Platinum–Palladium Alloy Nanodendrites with Various Compositions Using Amphiphilic Triblock Copolymers

Abstract: In a recent study, we demonstrated that Pluronic F127 triblock copolymer plays a critical role in the formation of dendritic Pt nanostructures (L. Wang, Y. Yamauchi, J. Am. Chem. Soc. 2009, 131, 9152-9153). Herein, we expand this concept to produce novel dendritic Pt-Pd alloy nanoparticles. In this paper, a very simple, one-step and efficient route is proposed to directly produce dendritic Pt-Pd alloy nanoparticles with high surface area in high yield, which is carried out simply by stirring an aqueous solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
54
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 65 publications
2
54
0
Order By: Relevance
“…Pt-based bimetallic NPs are a promising for use as catalysts in methanol and hydrogen oxidation, because of ideal electrochemical properties such as chemical inertness and high catalytic activity [11][12][13]. The high cost of rare Pt, however, is a significant hurdle, and many efforts have focused on the development of novel Pt-based nanomaterials with a core-shell and/or nanoporous structures in order to achieve a maximized surface area using a minimum amount of Pt [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Pt-based bimetallic NPs are a promising for use as catalysts in methanol and hydrogen oxidation, because of ideal electrochemical properties such as chemical inertness and high catalytic activity [11][12][13]. The high cost of rare Pt, however, is a significant hurdle, and many efforts have focused on the development of novel Pt-based nanomaterials with a core-shell and/or nanoporous structures in order to achieve a maximized surface area using a minimum amount of Pt [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their extremely large surface area that can greatly enhance the catalytic, electrochemical and drug delivery performance [13], NDs have recently attracted intensive research attention. Previously, NDs of metals and bimetals, including Pt [310], Pd [11], Au [1214], Au–Pd [11,15], Au–Pt [16,17], Pd–Pt [1,18,19], Pd–Co [20], Pd–Ni [20,21], and Pt–Cu [22], have been synthesized by a number of different approaches. In polymer science, the degree of branching (DB) is an important parameter that determines the chemical, physical and mechanical properties of dendritic polymers [23–27].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some researchers have shown that nanocatalysts with high dispersion and narrow size distributions stabilized by appropriate supports or capping materials can work under mild conditions with high activity and high selectivity when compared to conventional heterogeneous catalysts. It is known that the transition metal nanoparticles are effective catalysts, in which the shape, size, and surface structure of the solid supports all that contribute to the catalytic activity [1-4,9-13]. The supports usually are alumina, zeolite, and carbon materials that further include the carbon black, carbon nanotubes, graphene, and nanoporous carbon [14-20].…”
Section: Introductionmentioning
confidence: 99%